Maurice Maeterlinck and English and Anglo-Irish literature - Cnudde-Knowland, A; Cnudde-Knowland, Anne (1984)
Maurice Maeterlinck fulfilled a unique role in England at the end of the nineteenth century. He interpreted the symbolist vision for the English. His symbolist plays established the expressive power of a very simple style and offered an alternative to melodrama and realism. The mystical direction of his art appealed to the writers of the Celtic Renaissance. W.B. Yeats drew on Maeterlinck's theory and practice until the end of his career. During the 1890s, it was Maeterlinck's translation of the symbolist aesthetic in terms of the dramatic form which appealed to Yeats. The Shadowy Waters is Yeats's most extended exercise in a style indebted to "Symbolisme". During the years of Yeats's involvement in the Irish Literary Theatre, Maeterlinck's dramatic theories took over from his plays as the prime source of interest to Yeats. In addition, Yeats was strongly interested in the scenic innovations associated with Maeterlinck's work. The second chapter deals with the important speculations about anti-illusionist modes of dramatic presentation which were developed in France and England at the end of the nineteenth and at the beginning of the twentieth centuries, and which were anticipated in the prose writings of Charles Lamb. Chapter three consists of a discussion of Arthur Symons's unpublished play, Barbara Roscorla's Child, which registers Maeterlinck's influence. Chapter four examines Harley Granville Barker's encounter with Maeterlinck. It shows that Barker was particularly impressed by Maeterlinck's stress on inwardness. Barker's writings on acting and dramatic theory reflect his familiarity with Maeterlinck's Le Trésor des humbles, in particular the essay "Le Tragique quotidien". The chapter includes a discussion of Barker's unpublished play, A Miracle. Finally, the chapter on Henry James concentrates on the manner in which Maeterlinck provides one of the chief contexts of The Wings of the Dove. The frequent invocation of Maeterlinck's theory and practice is one of the important ways in which James suggests meaning and shapes the reader's response.